2020
DOI: 10.1007/s42399-020-00450-6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Reproducibility of Nuclear Imaging in the Assessment of Painful Hip and Knee Replacements

Abstract: Nuclear imaging is used in the evaluation of painful arthroplasties for diagnosing loosening or periprosthetic joint infection (PJI). The purpose of this systematic review is to depict the reproducibility of the various nuclear imaging modalities used in the assessment of painful hip and knee arthroplasties. A systematic review of the literature was conducted with a comprehensive search of MEDLINE to identify clinical studies investigating the intra-and inter-observer agreement of nuclear imaging modalities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…With high heterogeneity in the meta-regression, they highlighted how the heterogeneity of the studies was related to factors such as the type of radiotracer used, route of administration and method of image analysis. Verberne et al [ 28 ] reported on the intra- and interobserver agreement of nuclear imaging modalities for diagnosing infection and mechanical loosening in knee and hip arthroplasty patients. They found that SPECT/CT and FDG-PET/CT had substantial interobserver agreement for symptomatic hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With high heterogeneity in the meta-regression, they highlighted how the heterogeneity of the studies was related to factors such as the type of radiotracer used, route of administration and method of image analysis. Verberne et al [ 28 ] reported on the intra- and interobserver agreement of nuclear imaging modalities for diagnosing infection and mechanical loosening in knee and hip arthroplasty patients. They found that SPECT/CT and FDG-PET/CT had substantial interobserver agreement for symptomatic hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…To date, published systematic reviews related to painful arthroplasty are scarce: Barnsley et al [ 26 ] analysed two studies that used SPECT/CT as an index test (sensitivity 0.86, specificity 0.93); Peng et al [ 27 ] reported an analysis of sixteen papers; however, they did not separate the results for knee and hip prostheses. Verberne [ 28 ] conducted an analysis regarding the intra- and interobserver agreement of different nuclear medicine techniques in septic and aseptic symptomatic hip and knee replacements.…”
Section: Introductionmentioning
confidence: 99%